A new genus of compactopediina (coleoptera: staphylinidae) associated with longipeditermes (isoptera: termitidae) in peninsular Malaysia with a key to and phylogenetic analysis of all genera of the subtribe - Hashim, Rosli; Maruyama, M.; Kanao, T. (2011)
Kistnerella malayensis Kanao & Maruyama, gen. et sp.n. (Coleoptera: Staphylinidae: Aleocharinae) is described from Ulu Gombak, Selangor, Peninsular Malaysia. This new genus belongs to the termitophilous subtribe Compactopediina in the tribe Aleocharini, and is associated with Longipeditermes longipes (Haviland, 1889) (Isoptera: Termitidae: Nasutitermitinae). A key to the genera in Compactopediina is given. The phylogenetic relationships of the genera are investigated, and the host termite relationships and the systematic position of Compactopediina are discussed.